Gender and climate change adaptation in Uganda: Insights from Rakai - Kristjanson, Patricia; Bernier, Quinn; Bryan, Elizabeth; Ringler, Claudia; Meinzen-Dick, Ruth S.; Ampaire, Edidah; Kovarik, Chiara; Haglund, Eric; Quiros, Carlos; Herrero, Mario; Rufino, Mariana; Silvestri, Silvia; et al. (International Food Policy Research Institute, 2015)
Differences in the roles and responsibilities of men and women in farm households are likely to influence their capacity to adapt to climate change as well as the choice of adaptation strategies. However, governments, development agencies, and NGOs often lack the information needed to facilitate gender-sensitive adaptation to climate change. This brief summarizes research on key gender-related findings regarding climate change perceptions, adaptation strategies and information needs based on an intra-household survey of women and men in Rakai in south-central Uganda, one of the sites where the CGIAR Research Program on Climate Change, Agriculture and Food Security (CCAFS) is working. We asked the same set of questions to both women and men. The similarities and differences in their answers provide important insights for the design of policies and programs to meet their specific needs.